RISK ASSOCIATED WITH THE HIGH CONSUMPTION OF ULTRA-PROCESSED FOODS AND LOW INTAKE OF UNPROCESSED FOODS: A LONGITUDINAL ANALYSIS. (CIPEEX, 2025)
Dietary habits are frequently reported as determinants of health over time, including high consumption of ultra-processed foods (UPF) and low intake of unprocessed foods, as potential risk factors for quality of life (QoL). Based on this, our objective was to evaluate the association between regular UPF consumption and irregular intake of fruits and/or fruit salads, vegetables, and legumes with self-reported QoL among staff of the Federal Network of Professional, Scientific, and Technological Education (RFEPCT) in Brazil. This is a longitudinal study using a database entitled Quality of Life in Education in Brazil (QoLe-BRA). The first data collection in 2022 included 1,563 staff members, with 600 responding again in 2023. The questionnaires administered were the National School Health Survey (PeNSE) (dietary questions) and the World Health Organization Quality of Life (WHOQOL-bref) (quality of life). Both questionnaires are validated instruments. Dietary questions were analyzed based on consumption over the past seven days, with irregular consumption defined as 0–4 days and regular consumption as 5–7 days. Statistical analysis was conducted by calculating relative risk using the Generalized Estimating Equations (GEE) method, with a Poisson regression model and robust variance. Initially, the median scores of the WHOQOL-bref domains—physical, psychological, social relationships, environment, and total score—were calculated to define cut-off points for ‘high’ and ‘low’ QoL, with the latter used as the outcome in statistical analyses. Results showed that female participants had a higher risk of low QoL in the physical (RR = 1.19; p = 0.004) and psychological (RR = 1.17; p = 0.021) domains compared to males. Staff aged 60 years or older showed a lower risk of low QoL in the psychological domain (RR = 0.63; p = 0.021), indicating advanced age as a protective factor. Regular UPF consumption was associated with higher risk of low QoL in the physical (RR = 1.27; p < 0.001), psychological (RR = 1.19; p = 0.003), environment (RR = 1.13; p = 0.049) domains and total score (RR = 1.17; p = 0.020). Regular fast food consumption was also linked to higher risk of low QoL in the physical domain (RR = 1.29; p = 0.047). Regarding unprocessed foods, irregular consumption of vegetables and/or legumes increased the risk of low QoL across all domains: physical (RR = 1.20; p = 0.001), psychological (RR = 1.23; p < 0.001), social relationships (RR = 1.14; p = 0.005), and environment (RR = 1.23; p = 0.001). Similarly, irregular consumption of fresh fruits or fruit salads was associated with higher risk of low QoL in four domains: physical (RR = 1.18; p = 0.002), psychological (RR = 1.13; p = 0.009), environment (RR = 1.13; p = 0.014), and total score (RR = 1.13; p = 0.012). Regular consumption of UPF and low intake of fruits, fruit salads, vegetables, and/or legumes were associated with worse QoL, highlighting the importance of adopting healthy eating habits to promote staff well-being.